ChemInform Abstract: Asymmetric Synthesis of 3, 3′‐Pyrrolidinyl‐dispirooxindoles via a One‐Pot Organocatalytic Mannich/Deprotection/Aza‐Michael Sequence. Issue 23 (May 2016) - Zhao, Kun; Zhi, Ying; Li, Xinyi; Puttreddy, Rakesh; Rissanen, Kari; Enders, Dieter
Abstract: Using (DHQD)2 PHAL as the catalyst, this scalable protocol provides access to a new series of the title compounds in high yields and with excellent stereoselectivities via the novel organocatalytic reaction sequence.